The Role of Speech-language Pathologists in the Hospitals of Pakistan - Mehwish Zikria; Nazia Mumtaz; Ghulam Saqulain; Muhammad Naveed Babur (Iranian Rehabilitation Journal, 2021)
Objectives: This study aimed to assess the knowledge and perception of the role of speech therapists by other medical professionals in public hospitals. Methods: This cross-sectional study recruited 200 healthcare professionals with >1year of job experience at the workplace of both genders and any age. Besides, the study subjects were selected using a non-probability convenience sampling approach. The study sample was recruited from 25 District and Tehsil Headquarter Hospitals from April 1, 2019, to September 30, 2019. A basic demographic datasheet and the Knowledge, Attitude, and Practices (KAP) survey were used for data collection. Statistical analysis was performed in SPSS. Results: Out of the total 200 eligible professionals from different departments, the Mean±SD scores of the responses were highest (75.14±24.87) in pediatric medical professionals. Moreover, the lowest scores (46.70±0.01) concerned Intensive Care Unit (ICU) experts; this difference was statistically significant (P<0.001). Similarly, a significantly higher Mean±SD score of 74.05±20.04 was noted for those working day shifts, compared to that of (35.01±8.52) those working in night shifts (P<0.001). Discussion: The knowledge and perception of different healthcare professionals serving in public hospitals vary regarding the role of SLPs. Such differences concern their profession, with pediatrics presenting the highest level of understanding, followed by general medicine. However, psychiatry and ENT professional provided the least understanding in this area. The professionals working in day shifts suggested better knowledge and perception, compared to night shifts staff.